2017
DOI: 10.1080/07359683.2017.1310551
|View full text |Cite
|
Sign up to set email alerts
|

“On the doctor's orders”: A pilot study of the effects of website marketing for medical specialist providers under gatekeeping arrangements

Abstract: Websites from medical specialist providers are becoming increasingly marketing oriented, but there exists a paucity of empirical research on the effects. This experimental study explored effects of exposure to real websites from medical specialist providers among Dutch adults under physician gatekeeper arrangements. Exposure led to a stronger intention to seek treatment from the specialist provider and motivation to rely on the providers' claims. Weaker to absent effects were found for intention to question th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nevertheless, in relation to the specific subject of this study, there is limited research with regards to offering an overview of the internet presence of healthcare SMEs and the multilingual dissemination of their corporate information as well as the variables that influence these factors. However, some authors (Budiman et al, 2019;Cermak & Smutny, 2017;Pollard, 2000;Zwier, 2017) outline the importance of websites in medical markets as they serve as promotional mediums, improve communication, enhance business process, and often represent the first contact of consumers with the companies, a key element for customer satisfaction. In contrast, other studies remark the importance of offering multilingual and transcreated contents in this sector (Macario & Boyte, 2008;Olvera-Lobo & García-Santiago, 2019;Rivera et al, 2016), as cultural adaptation is particularly relevant for fields often dealing with sensitive content such as the healthcare sector.…”
Section: Website Translation and Localizationmentioning
confidence: 99%
“…Nevertheless, in relation to the specific subject of this study, there is limited research with regards to offering an overview of the internet presence of healthcare SMEs and the multilingual dissemination of their corporate information as well as the variables that influence these factors. However, some authors (Budiman et al, 2019;Cermak & Smutny, 2017;Pollard, 2000;Zwier, 2017) outline the importance of websites in medical markets as they serve as promotional mediums, improve communication, enhance business process, and often represent the first contact of consumers with the companies, a key element for customer satisfaction. In contrast, other studies remark the importance of offering multilingual and transcreated contents in this sector (Macario & Boyte, 2008;Olvera-Lobo & García-Santiago, 2019;Rivera et al, 2016), as cultural adaptation is particularly relevant for fields often dealing with sensitive content such as the healthcare sector.…”
Section: Website Translation and Localizationmentioning
confidence: 99%
“…Hyder and Fregidou-Malama (2009) observed that offering healthcare is rife with uncertainty, and therefore it becomes important for service providers to build trust in what being delivered. Zwier (2017) observed that Dutch patients tend to depend on the website marketing of private medical specialist service providers. Service researchers, however, have found that customers rely on information that is circulated by word-of-mouth (WOM) to reduce the risk and uncertainty involved in buying a service offering (Berry & Parasuraman, 1991;Chaniotakis & Lymperopoulos, 2009).…”
Section: Emerging Markets and Institutional Constraintsmentioning
confidence: 99%
“…Patients usually use information on the web to gain insight into their diseases and treatments. They may choose their healthcare provider according to the information they find, [ 1 , 2 ] request appointments online, use telemedicine services, [ 3 ] or are interested in wearable health devices with transmission of medical information for smart healthcare purposes. [ 4 6 ] For referring physicians, institutional websites offer information on how to refer patients.…”
Section: Introductionmentioning
confidence: 99%